As práticas da Terapia Ocupacional na Atenção Primária à Saúde à luz do Método Terapia Ocupacional Dinâmica: diálogos possíveis - Luiz, Patricia Moreira Dos Santos (Universidade Federal de São Carlos, 2025)
This work explores the interface between the Dynamic Occupational Therapy Method (MTOD) and Primary Health Care (PHC). The study highlights that both MTOD and PHC share similar objectives, such as promoting autonomy, addressing the social and territorial context, providing comprehensive and expanded care, and emphasizing people’s social participation. Objective: To understand the common aspects between the theoretical and methodological references of MTOD and PHC, as well as to systematize the theoretical convergences resulting from this association. Methodology: A cross-sectional exploratory study was conducted using a qualitative approach. The research was carried out within the Primary Health Care network of a municipality in the interior of São Paulo, with the participation of occupational therapists working in PHC in this municipality. One professional from each health region was invited to participate. Regarding research procedures, semi-structured interviews and participant observation in their work environments were conducted. Results: The data were analyzed based on the fundamentals of MTOD identified in the participants’ statements, which included: the expansion and potential construction of daily life, the target subject with needs and/or desires, health, activities, social insertion, and therapist training. The findings revealed a convergence between the practices performed by occupational therapists in PHC and the principles of MTOD. Despite challenges in establishing these associations, subtle connections were identified, including: target subject and gateway; health and comprehensiveness; social insertion and community orientation; activities and comprehensiveness; and education and longitudinality. Conclusion: This research identified commonalities between the theoretical and methodological references of MTOD and PHC. It contributed to a deeper understanding of the role of occupational therapists in this context, offering insights for professionals in different areas. Furthermore, it provided professionals who use MTOD with the opportunity to recognize the interfaces of this approach with theoretical frameworks from other disciplines. The study underscores the need for further research to deepen knowledge and address gaps in the literature.
Occupational Therapy practices in Primary Health Care in light of the Dynamic Occupational Therapy Method: possible dialogues
Keywords: Atenção primária à saúde; Terapia ocupacional; Método terapia ocupacional dinâmica; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL